Check the picture below
the triangles are similar, the angles are congruents then
so... just add them up, and divide by 2, or set them as rational
The probability of at least 6 failures in 7 trials of a binomial experiment in which the probability of success in any one trial is 9% will be <u>0.000343311 %</u>
<h3>What is the probability?</h3>
Probability is synonymous with possibility. It is concerned with the occurrence of a random event.
Probability can only have a value between 0 and 1. Its simple notion is that something is very likely to occur. It is the proportion of favorable events to the total number of events.
No of failure,n = 7
No of trials,x≥6
A binomial probability is represented as;
![\rm P(x) = nC_x p^z(1-p)^{n-r}](https://tex.z-dn.net/?f=%5Crm%20P%28x%29%20%3D%20nC_x%20p%5Ez%281-p%29%5E%7Bn-r%7D)
Substitute the given data;
![P(x \geq 6) = 7C_6 \times 9^6 \times 91-9)^{7-6} +7C_7 (9)^7+(1-9)^{(7-7)}](https://tex.z-dn.net/?f=P%28x%20%5Cgeq%206%29%20%3D%207C_6%20%5Ctimes%209%5E6%20%5Ctimes%2091-9%29%5E%7B7-6%7D%20%2B7C_7%20%289%29%5E7%2B%281-9%29%5E%7B%287-7%29%7D)
![\rm P(x \geq 6) = 0.000000343311 \\\\ P(x \geq6)=0.000343311 \%](https://tex.z-dn.net/?f=%5Crm%20P%28x%20%5Cgeq%206%29%20%20%3D%200.000000343311%20%5C%5C%5C%5C%20P%28x%20%5Cgeq6%29%3D0.000343311%20%5C%25)
Hence,the probability of at least 6 failures in 7 trials of a binomial experiment in which the probability of success in any one trial is 9% will be <u>0.000343311 %</u>
To learn more about probability, refer to the link: brainly.com/question/795909.
#SPJ1
Answer: the fixed cost to rent the limousine is $200
Step-by-step explanation:
Let x represent the fixed cost rent the limousine.
Let y represent the cost of of hiring the driver of the limousine per hour.
It cost $500 to rent a limousine for 5 hours. This means that
x + 5y = 500 - - - - - - - - - - -1
It costs 800 to rent a limousine for 10 hours. This means that
x + 10y = 800 - - - - - - - - - - -2
Subtracting equation 2 from equation 1, it becomes
- 5y = - 300
y = - 300 /- 5
y = 60
Substituting y = 60 into equation 1, it becomes
x + 5 × 60 = 500
x + 300 = 500
x = 500 - 300
x = 200
Answer:
136 ft^2
Step-by-step explanation:
Surface area = 2 [ (l*w) + (l*h) + (w*h) ]
= 2 [ (8*3) + (8*4) + (4*3) ]
= 136 ft^2
Answer:
<h2>YES</h2><h2>NO</h2><h2>YES</h2><h2>NO</h2>
Step-by-step explanation:
![3x+7\\\\3\left(x+\dfrac{7}{3}\right)=(3)(x)+(\not3)\left(\dfrac{7}{\not3}\right)=3x+7\qquad\boxed{YES}\\_{\text{used the distributive property: a(b + c) = ab + ac}}\\\\x+x+x+5+1=(x+x+x)+(5+1)=3x+6\neq3x+7\qquad\boxed{NO}\\\\8x+3-5x+4=(8x-5x)+(3+4)=3x+7\qquad\boxed{YES}\\\\7x+3\neq3x+7\qquad\boxed{NO}](https://tex.z-dn.net/?f=3x%2B7%5C%5C%5C%5C3%5Cleft%28x%2B%5Cdfrac%7B7%7D%7B3%7D%5Cright%29%3D%283%29%28x%29%2B%28%5Cnot3%29%5Cleft%28%5Cdfrac%7B7%7D%7B%5Cnot3%7D%5Cright%29%3D3x%2B7%5Cqquad%5Cboxed%7BYES%7D%5C%5C_%7B%5Ctext%7Bused%20the%20distributive%20property%3A%20a%28b%20%2B%20c%29%20%3D%20ab%20%2B%20ac%7D%7D%5C%5C%5C%5Cx%2Bx%2Bx%2B5%2B1%3D%28x%2Bx%2Bx%29%2B%285%2B1%29%3D3x%2B6%5Cneq3x%2B7%5Cqquad%5Cboxed%7BNO%7D%5C%5C%5C%5C8x%2B3-5x%2B4%3D%288x-5x%29%2B%283%2B4%29%3D3x%2B7%5Cqquad%5Cboxed%7BYES%7D%5C%5C%5C%5C7x%2B3%5Cneq3x%2B7%5Cqquad%5Cboxed%7BNO%7D)